Evaluation of the information level on doping with Serbian pharmacists - Antić, Dušan (Archives of Pharmacy, 2022)
The aim of this research was to establish pharmacists’ level of information, knowledge and attitudes towards doping. This survey was performed as a transverse study with empirical characteristic and included 173 participants of different sex and age. With the purpose of collecting data, a questionnaire was used as a non-standard research technique. The small number of respondents was informed about the Prohibited list (9.5%). Pharmacists gained knowledge and pieces of information about doping from media (34.8%) and internet (33.6%). The majority of participants knew that urine is the most common sample for doping analysis (86.3%). The correct answers that spironolactone, pseudoephedrine, tuaminoheptane and intravenous corticosteroids are prohibited in sport were given by less than half of respondents (36.6%, 19.9%, 26.7% and 37.8%, respectively). Also, that inhaled salmeterol, inhaled corticosteroids, creatine and diclofenac are allowed in sport knew 42%, 40.6%, 47.7% and 52.9%, of respondents, respectively. The correct answer that athletes are allowed to use the medicine which contains doping substance, but only if they have granted Therapeutic Use Exemption, was given by 64.1% of participants. Pharmacists had polyvalent attitudes towards doping in sports. The results of this study show that pharmacists have insufficient information level on different aspects of doping. Since all patients, as well as athletes, are treated by them, their knowledge should be on higher level in order to prevent accidental doping positive cases. These results could be a good direction for planning actions which would be directed to the education of pharmacists about doping.